Underage Mothers - Turan, Nurşen; Dokgöz, Halis (The Bulletin of Legal Medicine, 2007)
Every person between 0-18 years old is respected as child according to Children Wellness Protocol. To be pregnant and to give birth are not less among children at these age group in the world. Children of underage mother are less healthy and with more risk of abuse and nourishment problem than other children. They live in low socioeconomical level and most of them may have criminal behaviour in future. In Turkey, data and statistical knowledge about teenage mother is not adequate. This artical gives attention to importance of legal arrangement which affects health of underage mother and her child. New legal arrangements about underage mother must be put into practice in order to protect underage mother and her child urgently and more studies are needed to determine situation of underage mothers in Turkey. Key words: Child, underage mothers, pregnancy